2018
DOI: 10.3847/1538-4357/aa9cec
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Galactic Halo with APOGEE. I. Chemical and Kinematical Investigation of Distinct Metal-poor Populations

Abstract: We find two chemically distinct populations separated relatively cleanly in the [Fe/H]-[Mg/Fe] plane, but also distinguished in other chemical planes, among metal-poor stars (primarily with metallicities < -[ ] Fe H 0.9) observed by the Apache Point Observatory Galactic Evolution Experiment (APOGEE) and analyzed for Data Release 13 (DR13) of the Sloan Digital Sky Survey. These two stellar populations show the most significant differences in their [X/Fe] ratios for the α-elements, C+N, Al, and Ni. In addition t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
125
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(166 citation statements)
references
References 87 publications
38
125
2
1
Order By: Relevance
“…fers from that of the Milky Way (e.g., Tolstoy et al 2009). The accreted origin of the GCs that are kinematically associated with GE, H99 and Seq is further confirmed by the fact that their position in the [Si/Fe] plane mimics that of field populations linked with past accretion events (Hayes et al 2018;Mackereth et al 2019). We calculate the mean [Si/Fe] abundace given by GCs in the -1.5 < [Fe/H] < -1 regime for both our accreted and in situ populations, and find that the accreted groups display on average [Si/Fe] = +0.17±0.05, whereas the in situ subgroups display a higher average abundance [Si/Fe] = +0.25±0.03.…”
Section: Accreted Subgroupsmentioning
confidence: 73%
“…fers from that of the Milky Way (e.g., Tolstoy et al 2009). The accreted origin of the GCs that are kinematically associated with GE, H99 and Seq is further confirmed by the fact that their position in the [Si/Fe] plane mimics that of field populations linked with past accretion events (Hayes et al 2018;Mackereth et al 2019). We calculate the mean [Si/Fe] abundace given by GCs in the -1.5 < [Fe/H] < -1 regime for both our accreted and in situ populations, and find that the accreted groups display on average [Si/Fe] = +0.17±0.05, whereas the in situ subgroups display a higher average abundance [Si/Fe] = +0.25±0.03.…”
Section: Accreted Subgroupsmentioning
confidence: 73%
“…What about other potentially major accretion sources? Studies of metal-poor stars have uncovered two chemically distinct populations in the MW (e.g., Nissen & Schuster 2010;Hawkins et al 2015;Hayes et al 2018). These two populations are (using the definitions from Fernández-Alvar et al 2018; Hayes et al 2018) a "low-magnesium" halo population, thought to be accreted satellite galaxy debris, and a "highmagnesium" population, which continues the chemical trends of the thick disk and has the chemistry expected of the classical halo.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of metal-poor stars have uncovered two chemically distinct populations in the MW (e.g., Nissen & Schuster 2010;Hawkins et al 2015;Hayes et al 2018). These two populations are (using the definitions from Fernández-Alvar et al 2018; Hayes et al 2018) a "low-magnesium" halo population, thought to be accreted satellite galaxy debris, and a "highmagnesium" population, which continues the chemical trends of the thick disk and has the chemistry expected of the classical halo. The [X/Fe] ratios of TriAnd stars in (C+N), K, Mn, and Ni are 0.2-0.4 dex higher than the population of MW field stars thought to be accreted halo stars, and are also differentiated from the more classical halo population (and thick disk), which have high α-element abundances.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, α peak elements, especially magnesium, can help distinguishing both populations. For example, using data from APOGEE Hawkins et al (2015) and Hayes et al (2018) have shown that for [Fe/H] −0.7 there are two distinct populations: an [α/Fe] poor sequence with zero net rotation, which is consistent with stars being mainly accreted from small dwarf satellites whose stellar populations were formed in the first few Gyr of the universe; and an [α/Fe] rich sequence, which has some net rotation and is kinematically colder than the [α/Fe] poor sequence. Hawkins et al (2015) point out that these [α/Fe] rich stars could come from either the thick disc or from some form of in-situ (in their words "canonical") halo population.…”
Section: Introductionmentioning
confidence: 99%